Recycling workers and possible articulations between precarious work and gender relationships (Cadernos de Psicologia Social do Trabalho, 2012)
This article describes an ethnography conducted with recycling workers in a city in Porto Alegre's metropolitan area. It aims at understanding how precarious labor relationships affect gender relationships, questioning tasks culturally assumed as masculine and seeing gender hierarchies through another perspective. We will analyze two workplaces frequented by recycling workers: training sessions and a recycling unit. In our analysis we will indicate how much traditional masculine and feminine roles are transformed in order to fulfill workers needs to earn enough to sustain themselves.